Management of minor burns during the COVID-19 pandemic: A patient-centred approach. (June 2021) - Farid, Mohammed; Al Omran, Yasser; Lewis, Darren; Kay, Alan
Introduction: The UK government introduced lockdown measures on 23 March 2020 due to the first wave of the COVID-19 pandemic. A restructuring of clinical services was necessary to accommodate mandatory changes while also maintaining the best possible standards for patient care. The present study explored the initial management, follow-up and patient-reported outcomes of burn injuries <15% total body surface area (TBSA) during the height of the COVID-19 lockdown at a tertiary burns centre. Methods: A retrospective review of all adult patients with burns <15% TBSA during the national lockdown (23 March 2020 to 10 May 2020) was undertaken at The Queen Elizabeth Hospital Birmingham (QEHB), UK. All referrals from non-QEHB telemedicine (external) or QEHB emergency (internal) departments were reviewed for management, length of hospital stay and pattern of follow-up (ward attender, self-care, community or outreach nurses). A telephone survey based on a structured questionnaire was conducted to establish patients' satisfaction. Results: A total of 84 burn patients were included in the study. The mean age was 39 years (age range = 19–91 years) and the male:female ratio was 4:1. Patients were managed non-operatively (n = 69, 82%) or operatively (n = 15, 18%). Patients attended the ward attender acute burns clinic only once (n = 36, 61%). The telephone survey captured 70% (n = 59) of the study population and 57 patients (97% of respondents) were pleased with the ongoing care and burn healing. Conclusion: The integration of patient led self-care, reduction in admissions, minimal clinics attendance and a telemedicine follow-up is an effective model for small burns management during the COVID-19 pandemic. A high degree of patient satisfaction was achieved with continuous and approachable communication channels with the burn multidisciplinary team. We continue to implement this effective model of burns management throughout the COVID-19 pandemic and the subsequent period. Lay Summary: The lockdown measures due to the first wave of COVID-19 pandemic affected the way we manage all medical emergencies including burns. The initial management, follow-up and patient satisfaction for small burn injuries during lockdown has not been reported previously. The aim of this study is to examine the outcome in terms of small burn management, hospital stay, number of clinic reviews, healing and patient satisfaction during the lockdown period in a burn centre in the UK. This would look at the need for operations and whether patients stayed longer if they required an intervention. We reviewed adult patients with small burns during the national lockdown (23 March 2020 to 10 May 2020) at The Queen Elizabeth Hospital Birmingham (QEHB). All referrals from telemedicine, referral system (external) or QEHB (internal) were reviewed for management, length of hospital stay and pattern of follow-up. Patients were reviewed in the acute burns clinic and given advice for burn management and dressing for self-care. Follow-up was mostly via email (telemedicine) A telephone survey based on a structured questionnaire was conducted to find out patients' satisfaction. Four times more men than women had small burns during the lockdown period. The average age was 39 years. The majority were managed conservatively with dressings (82%) and a small proportion required an operation (18%). Most patients attended the acute burns clinic only once (61%) for initial assessment and management. The telephone survey captured 70% of patient and 97% of respondents were pleased with the care and burn healing. The integration of patient-led self-care, reduction in admissions, minimal clinics attendance and a telemedicine follow-up is an effective model for burns management during the COVID-19 pandemic. A high degree of patient satisfaction was achieved with continuous and approachable communication channels with burn multidisciplinary team. We continue to implement this effective model of burns management throughout the COVID-19 pandemic and the subsequent period.